Higher education as engine of economic growth and regional integration: The emergence of the new APEX university in Malaysia - Campbell, James (College of Law, Government and International Studies, Universiti Utara Malaysia., 2010)
The USM APEX strategy and engagement with building alliances, partnerships, collaborations and tying this to a moral project of sustainability and serving the „bottom billions‟ is a rational and astute response to the practical problems that USM and Malaysia faces within current globalization. In essence APEX is an engagement with transformation of higher education in an increasingly complex and interconnected global environment. APEX is an attempt to show the way the higher educational institutions can provide leadership and legitimacy in a globalized and networked environment of the new economy and new information age. The recognition that higher educational reform in Malaysia must be holistic and that it must combine effort to change mindsets as well as protect culture and values are policy prescriptions that animate Malaysian public policy and are critical to USM‟s APEX agenda. The dynamics and forces of globalization have lead to a radical rethink in respect to the role of the University in contemporary society. While many higher educational institutions appear to be following the prescriptions of neo-liberal reform captured in the model of the Washington Consensus others such as USM are seeking an alternative path to reform based on an engagement with local values and needs. The questions that animate this paper in reference to the USM reform model is to what extent USM can maintain its legitimacy reputation and rank given its desire to reform and challenge the neo-liberal status quo. Realising reform for a „New Asian Century‟ in the higher educational sector requires a rigorous assessment of how educational institutions can maintain their legitimacy, reputation and sense of position as they seek to change.